QUAKER - LIAM MCILVANNEY (HARPERCOLLINS Publishers, 2019)
Glasgow, 1969. In the grip of the worst winter for years, the city is brought to its knees by a killer whose name fills the streets with fear: the Quaker. He takes his next victim, the third woman from the same nightclub, and dumps her in the street like rubbish. The police are left chasing a ghost, with no new leads and no hope of catching their prey. DI McCormack, a talented young detective from the Highlands, is ordered to join the investigation. But his arrival is met with anger from a group of officers on the brink of despair. Soon he learns just how difficult life can be for an outsider. When another woman is found murdered in a tenement flat, it's clear the case is by no means over. From ruined backstreets to the dark heart of Glasgow, McCormack follows a trail of secrets that will change the city and his life forever